2021
DOI: 10.48550/arxiv.2102.06354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-trivial smooth families of $K3$ surfaces

Abstract: Let X be a complex K3 surface, Dif f (X) the group of diffeomorphisms of X and Dif f (X) 0 the identity component. We prove that the fundamental group of Dif f (X) 0 contains a free abelian group of countably infinite rank as a direct summand. The summand is detected using families Seiberg-Witten invariants. The moduli space of Einstein metrics on X is used as a key ingredient in the proof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Baraglia [3] and Lin [46] gave examples of smooth 1-connected 4-manifolds M for which π 2 (BDiff(M)) is not finitely generated, so the analogues of Theorems A and C fail in dimension 4. For 2n = 2, the result is well-known.…”
Section: Small Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baraglia [3] and Lin [46] gave examples of smooth 1-connected 4-manifolds M for which π 2 (BDiff(M)) is not finitely generated, so the analogues of Theorems A and C fail in dimension 4. For 2n = 2, the result is well-known.…”
Section: Small Dimensionsmentioning
confidence: 99%
“…Lemma 4. 3 Let M be a compact smooth manifold of dimension d ≥ 3 with π 1 (M) finite at all basepoints. Then the kth homotopy group of the total homotopy fibre of (22) is finitely generated for k ≥ 2 and finite for k = 1.…”
Section: The Case Of Finite Second Homotopy Groupmentioning
confidence: 99%
“…Small dimensions. Baraglia showed that π 2 (BDiff(M )) is not finitely generated for M a complex K3-surface [Bar21], so the analogues of Theorems A and C fail for closed simply connected 4-manifolds. It seems not to be known whether in this dimension Theorem C also fails in positive codimension.…”
Section: Infinite Fundamental Groupsmentioning
confidence: 99%